TO EVALUATE THE ANTIDEPRESSANT EFFECT OF APPLE AND ORANGE PULP IN MICE (Journal of Medical & Health Sciences Review, 2025)
Brain recession is one of the most extensive, persistant diseases determining temper, view, physical health and actions of a human being.The following research was done in order to investigate the anti-anxiety effects of severe and persistant use of apple and orange pulp in group of animals for experiment. We administered the juice from the fresh fruits of Malus domestica and citrus sinensis (1 ml and 2 ml per kilogram of weight). Dibenzoazepine (10 mg per kilogram per oral). Three series of animals were prepared, and one animal was in each series. Drugs and vehicles were administered before 60 min of experiments in acute study. Drugs and vehicles were provided in chronic study prior 60 mins for 15 days and on the fifteenth day last dose was administered. FST and TST for evaluation of anti-anxiety effects were done. (1)